2008
DOI: 10.1017/s000711450788634x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of apolipoprotein E genotype and dietary α-tocopherol on redox status and C-reactive protein levels in apolipoprotein E3 and E4 targeted replacement mice

Abstract: The molecular basis of the positive association between apoE4 genotype and CVD remains unclear. There is direct in vitro evidence indicating that apoE4 is a poorer antioxidant relative to the apoE3 isoform, with some indirect in vivo evidence also available. Therefore it was hypothesised that apoE4 carriers may benefit from a-tocopherol (a-Toc) supplementation. Targeted replacement mice expressing the human apoE3 and apoE4 were fed with a diet poor (0 mg/kg diet) or rich (200 mg/kg diet) in a-Toc for 12 weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 62 publications
2
9
0
1
Order By: Relevance
“…This would result in lower tissue α‐TOH, but potentially higher levels in the circulation. This is in line with our recent observations in apoE transgenic mice where significantly lower α‐TOH tissue levels were found in the lung of apoE4 compared with apoE3 mice although plasma α‐TOH concentrations were similar between the two genotypes 54. These data suggest that plasma vitamin E levels may not necessarily display peripheral vitamin E tissue status and may therefore be of limited validity.…”
Section: Apoe Genotype and Vitamin E Statussupporting
confidence: 90%
“…This would result in lower tissue α‐TOH, but potentially higher levels in the circulation. This is in line with our recent observations in apoE transgenic mice where significantly lower α‐TOH tissue levels were found in the lung of apoE4 compared with apoE3 mice although plasma α‐TOH concentrations were similar between the two genotypes 54. These data suggest that plasma vitamin E levels may not necessarily display peripheral vitamin E tissue status and may therefore be of limited validity.…”
Section: Apoe Genotype and Vitamin E Statussupporting
confidence: 90%
“…However, more recent evidence demonstrates the multifunctional nature of the apoE protein and the fact that the impact of genotype on disease risk may be in large part due to an impact on oxidative status or the immunomodulatory/ antiinflammatory properties of apoE (13). An increasing number of studies in cell lines (19)(20)(21), targeted replacement rodents (19,22), and human volunteers (23,24) indicate higher oxidative stress and a more proinflammatory state associated with the «4 allele. Furthermore, the apo «4 allele may be associated with impairment of endothelium-dependent arterial dilation (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…MT exhibits antioxidant (Miles et al 2000) and antiinflammatory properties (Inoue et al 2009). We have previously shown that the APOE4 genotype is associated with an altered inflammatory response ) and differences in the cellular oxidant/antioxidant status (Dietrich et al 2005;Jofre-Monseny et al 2008a;Huebbe et al 2007) in cultured cells, mice and humans. These differences in the inflammatory and oxidant/antioxidant status between the two genotypes may be partly related to differences in metallothionein levels.…”
Section: Discussionmentioning
confidence: 98%